Komunikasi Interpersonal Orang Tua pada Anak dalam Edukasi Pinjaman Online: Studi Kasus Terkait Interpersonal Power Orang Tua pada Keluarga Ekonomi Menengah ke Bawah - Panggah Lesmantoro; Arif Surya Kusuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The assumption in this research is how Generation Z, as digital natives, has become a generation that is familiar and easily accesses media such as online lending applications. Several studies have shown the pros and cons within the online lending culture. Furthermore, data from the OJK indicating that Gen Z is the largest contributor to bad credit highlights the urgency of conducting this research. In the process of digital media literacy, there are gaps between parents and Gen Z, known as the digital divide phenomenon. Within these conditions, online lending innovation emerges as problematic issue, particularly in a family context. The focus of this research is the tendency of interpersonal communication between parents and children regarding Interpersonal Power and which type of power is most suitable for educating children about online lending in lower-middle-class families. This study uses a qualitative method with a descriptive approach and the Interpersonal Power theory initiated by John R. P. French and Bertram Raven, adapted by Joseph A. Devito, to explain the online lending education processes conducted by parents for Gen Z. The results of this study indicate that not all types of power possessed by parents can be applied in lower-middle-class family conditions. Reward power, coercive power, and expert power are irrelevant to be applied in these families, whereas referent power and legitimate power proved to be the dominant powers used within the lower-middle-class family scope. These two powers produce a social approach that aligns with the socio-economic reality of lower-middle-class families, with referent power used to build awareness and legitimate power used for supervision.